A critical ANALYSIS OF Interplay BETWEEN Various components OF WORKING CAPITAL FOR MSMES’ ENGAGED IN PROJECT-BASED MANUFACTURING – INDIAN CONTEXT (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study involves an empirical analysis of  factors influencing cash holding by MSME’s  manufacturing substitutes for defence  aviation sub-assemblies in India. Quantitative  research methodology with correlation design  establishes the relation between cash holding  and the components of working capital. The  univariate data analysis indicates that cash  and cash equivalents constitute 14.14%,  inventory 24% and trade receivables 42  % of the current assets. The panel data  regression analysis with trade receivables as  the independent variable explains 50 % of the  variability of cash holding and has significant  impact on cash holding. The research is  unique as it focuses on the relationship of cash  holding with the working capital components  for low volume labour intensive project  nature of manufacturing by the MSMEs.
Keywords: Cash Holding; Working Capital Components; Project-Based Manufacturing